OS 33-06 IN PATIENTS WITH PRIMARY ALDOSTERONISM, OBSTRUCTIVE SLEEP APNOEA IMPROVES WITH TREATMENT BY ADRENALECTOMY OR MEDICAL THERAPY. (September 2016) - Wolley, Martin; Cowley, Diane; Ahmed, Ashraf; Gordon, Richard; Stowasser, Michael
Abstract : Objective: Obstructive sleep apnoea (OSA) is known to commonly co-exist with primary aldosteronism (PA), but it is unknown if treatment via mineralocorticoid receptor blockade or adrenalectomy (for aldosterone producing adenoma, APA), improves sleep apnoea parameters in these patients. We therefore aimed to determine if specific medical or surgical treatment of PA improves OSA, as measured by the apnoea hypopnoea index (AHI). Design and Method: Patients undergoing diagnostic workup for PA were recruited if they had symptoms suggestive of OSA. Patients with confirmed PA underwent polysomnography (PSG) at baseline and again at least 3 months after specific treatment for PA. Patients with severe OSA were referred for continuous positive airway pressure (CPAP) and only restudied with PSG if this had not yet commenced at the planned time of restudy. Results: Of 34 patients with PA, 7 (21%) had no evidence of OSA (AHI <5), 9 (26%) had mild (AHI 5 - 15), 8 (24%) moderate (AHI 15 - 30) and 10 (29%) severe OSA (AHI > = 30). Weight, body mass index tertile, and neck circumference correlated with the AHI. 20 patients had repeat PSG performed after treatment for PA (mineralocorticoid receptor antagonists in 13 with bilateral PA and adrenalectomy in 7 with unilateral PA). In this group the median (SD) AHI reduced from 22.5 (14.7) to 12.3 (12.1) (p = 0.018). There was a similar magnitude of fall between surgically and medically treated patients. There was no significant change in patient weight (95.2 kg vs 96.6 kg, p = 0.33; mean change +0.66 kg), however a small but significant reduction in neck circumference occurred (41.6 cm vs 41.2 cm, p = 0.012; mean change −0.56 cm). Conclusions: OSA is common in patients with PA, and improves with specific therapy for this disease. Aldosterone and sodium mediated fluid retention in the upper airways and neck region may be a potential mechanism for this relationship.